Pectinase immobilization on modified glass beads through salinization and its application in juice purification as a commercial activity - Dr. Hiral D. Trivedi; Dr. Dinesh S. Patel (The Bioscan, 2025)
The Pectinase enzyme was immobilized on glass beads in the current work using covalent coupling. Glass beads were utilized; they were purchased from scientific stationary. Covalent coupling rendered pectinase immobile. Using pectinase - loaded glass beads, different parameters were tuned and comparative studies were conducted following the immobilization procedure for more research. To further show that the support bead's enzyme was immobilized, FTIR & SEM analyses were conducted. Pectinase from it was used to purify fruit juice, specifically pineapple, watermelon, and sugarcane juice. Furthermore, because the immobilized enzyme can be reused in its whole, this study presents a novel development on the environmentally beneficial effects of immobilized enzymes.